1998
DOI: 10.4049/jimmunol.161.7.3575
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Activities of the gp130-Stimulating Designer Cytokine Hyper-IL-6

Abstract: IL-6 is a multifactorial cytokine mediating acute inflammatory responses in the liver. When IL-6 binds to a specific receptor (IL-6R), the IL-6/IL-6R complex associates with the signal transducer gp130, initiating intracellular signaling. A soluble form of the IL-6R (sIL-6R) renders target cells sensitive to IL-6 that do not express the IL-6R on their surfaces. A designer cytokine, termed Hyper-IL-6, consisting of IL-6 covalently linked to the sIL-6R was fully active on gp130-expressing cells at 100- to 1000-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In contrast, stimulation with the complex of IL-6 and sIL-6R activated all gp130 receptors on the cell surface. Moreover, stimulation with IL-6 alone led to the rapid internalization of the IL-6–mIL-6R–gp130 signalling complex, whereas stimulation with the IL-6–sIL-6R complex led to reduced gp130 internalization and therefore longer signalling duration; however, no qualitative differences between intracellular IL-6 classic signalling and trans-signalling pathways (for example, in terms of JAK–STAT and MAPK activation) were detected 57 , 58 . We concluded that cells stimulated via IL-6 trans-signalling showed a more sustained IL-6 response with a higher amplitude than cells expressing mIL-6R when stimulated with IL-6 in the absence of sIL-6R 54 .…”
Section: The Advent Of Il-6 Trans-signallingmentioning
confidence: 94%
“…In contrast, stimulation with the complex of IL-6 and sIL-6R activated all gp130 receptors on the cell surface. Moreover, stimulation with IL-6 alone led to the rapid internalization of the IL-6–mIL-6R–gp130 signalling complex, whereas stimulation with the IL-6–sIL-6R complex led to reduced gp130 internalization and therefore longer signalling duration; however, no qualitative differences between intracellular IL-6 classic signalling and trans-signalling pathways (for example, in terms of JAK–STAT and MAPK activation) were detected 57 , 58 . We concluded that cells stimulated via IL-6 trans-signalling showed a more sustained IL-6 response with a higher amplitude than cells expressing mIL-6R when stimulated with IL-6 in the absence of sIL-6R 54 .…”
Section: The Advent Of Il-6 Trans-signallingmentioning
confidence: 94%
“…To analyze whether recombinant IL-6 is able to stimulate thrombopoiesis after PHx, we treated mice with recombinant hyper-IL6 (hIL-6) because hIL-6 has a 10 times higher bioactivity than IL-6 alone and a longer bioavailability in vivo. (29) Although no differences in platelet counts could be observed after hIL6 treatment, enhanced platelet size was measured in hIL-6-treated mice compared to controls (Supporting Fig. S8A,B).…”
Section: Cytokine Signaling By the Il-6r And Stat Signaling Plays A C...mentioning
confidence: 91%
“…Since hepatocytes express more gp130 than IL-6R, the presence of IL-6 and sIL-6R results in greater gp130 activation and, therefore, higher IL-6 signal amplitude. Moreover, the IL-6/sIL-6R complex was shown to be internalized less efficiently than IL-6/IL-6R, resulting in longer IL-6 signal duration when mediated by trans-signaling [107]. Accordingly, hepatocytes permanently proliferated in IL-6/sIL-6R double transgenic mice in the absence of any liver insults but did not show any mitogenic response in IL-6 single transgenic mice.…”
Section: Involvement Of Growth Factors and Bioactive Molecules In The...mentioning
confidence: 97%